2007
DOI: 10.1021/jp0746190
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfine Coupling in Methyl Radical Isotopomers

Abstract: The hyperfine coupling constants (hfcs) of two methyl radical isotopomers, CH2Mu and CD2Mu, have been measured over a wide range of temperature in ketene and ketene-d2, from which the radicals were generated. The magnitudes of the hfcs of these muoniated methyl radical isotopomers are larger than those of CH3 and CD3 due to larger zero-point energy in the out-of-plane bending mode. In contrast to CH3 and CD3, where the coupling constants become smaller with increasing temperature, the negative hfcs of the muon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 64 publications
1
31
0
Order By: Relevance
“…7,8,10,11 An ALC signal appears as a "dip" in the time-integrated decay asymmetry at a particular value of the LF, corresponding to a resonant transfer of muon spin polarization from the backward to the forward direction as the magnetic field is varied. 8,11,13,14,20,31,32 In the present study, typically several sweeps of the LF range were carried out, in alternating directions, incremented in steps of about 100 G, depending on conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8,10,11 An ALC signal appears as a "dip" in the time-integrated decay asymmetry at a particular value of the LF, corresponding to a resonant transfer of muon spin polarization from the backward to the forward direction as the magnetic field is varied. 8,11,13,14,20,31,32 In the present study, typically several sweeps of the LF range were carried out, in alternating directions, incremented in steps of about 100 G, depending on conditions.…”
Section: Methodsmentioning
confidence: 99%
“…12 Since the electronic Hamiltonian is isotopically invariant within the Born-Oppenheimer (BO) approximation, the effect of isotopic substitution on torsional barriers is due to differences in zero-pointenergy (ZPE) at potential extrema. 12,14,[16][17][18][19][20] Given that the muon mass is only one-ninth that of the proton, much larger changes in ABSTRACT: Reported here is the first μSR study of the muon (A μ ) and proton (A p ) β-hyperfine coupling constants (Hfcc) of muoniated sec-butyl radicals, formed by muonium (Mu) addition to 1-butene and to cis-and trans-2-butene. The data are compared with in vacuo spinunrestricted MP2 and hybrid DFT/B3YLP calculations reported in the previous paper (I), which played an important part in the interpretation of the data.…”
Section: Introductionmentioning
confidence: 99%
“…The vibrational properties of the bound muonium atom in excited vibrational states of the MuCH 2 CH 2 • radical were later studied theoretically, in which profound anharmonicity of the C-Mu bond was indicated. Using an adept strategy in which muonium was added initially to pure liquid ketene (H 2 C=CO), the muonated methyl radical was detected (MuCH 2 • ) and also the dideuterated version (MuCD 2 • ), formed in liquid ketene-d 2 (D 2 C=CO) 40 . On the basis of ESR and μSR measurements, analyses have been made of the observed temperature dependences of the proton, deuteron and muon hyperfine couplings in terms of the outof-plane vibrations of the various hydrogen isotopes bound to the central carbon atom on which the unpaired electron is formally contained in a 2p z orbital.…”
Section: Structural and Mechanistic Studies Of Radicalsmentioning
confidence: 99%
“…In fact, Mu has long been used to understand nuclear quantum effects in chemical reactions including tunneling and quantized vibrations and there have been reported many studies showing very large isotope effects so far [3,4]. In particular, due to its extremely light mass and very large vibrational amplitudes, Mu-containing molecules frequently show a significantly delocalized character in molecular structures compared to hydrogen-and deuteriumcontaining molecules [5][6][7][8][9][10][11][12][13][14][15]. Alternatively, it has been reported that Mu can be localized in a very different region of the potential energy surface compared to hydrogen and deuterium cases due to multi-dimensional effects.…”
Section: Introductionmentioning
confidence: 99%